PENGUNGKAPAN PRIBADI REMAJA KELUARGA BROKEN HOME - Melita, Yerah; Elisabeth, Melva (Istek Widuri Jakarta, 2024)
A family is a group of individuals living together, bound by blood relations and marital ties. Withinfamily life, misunderstandings, differing opinions, and contrasting perspectives often arise, leading todisputes or conflicts among family members. In some cases, these disagreements escalate and, if notmanaged effectively, result in separation or divorce. Such familial conflicts can cause fractures or criseswithin the family structure, ultimately leading to the dissolution of the household, commonly referred toas a